THE EFFECT OF WORK LIFE BALANCE AND EMPLOYEE ENGAGEMENT ON PERFORMANCE THROUGH WORK DISCIPLINE - Ilfana, Azza Nur; Setiani, Setiani (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study aims to analyze the effect of Work Life Balance and Employee Engagement on the Performance of Employees of PT Kereta Api Indonesia (Persero) Operational Area 8 Surabaya, as well as the role of Work Discipline as an intervening variable. This study uses a quantitative \approach with explanatory analysis methods to explain the relationship between the variables studied. The population in this study was all employees of PT KAI DAOP 8 Surabaya, with certain criteria adjusted to the research objectives. Sampling was carried out using methods relevant to the quantitative research approach. Data were collected through questionnaires and analyzed using SmartPLS 3.0 software to test the relationship between variables. The results show that Work-Life Balance does not have a significant effect on Employee Performance, but Employee Engagement has a positive and significant effect on Employee Performance. In addition, the Work Discipline variable is able to mediate the positive and significant effect of Work-Life Balance and Employee Engagement on Employee Performance. These findings indicate that increasing employee engagement and implementing good discipline can be effective strategies for improving performance in the work environment of PT KAI DAOP 8 Surabaya.